The value and prognostic significance of neutrophil / lymphocyte ratio in predicting pancreatic fistula in patients undergoing pancreaticoduodenectomy for periampullary tumors - Bahadir Arikan, Turkmen; Mutevelli Sozuer, Erdogan; Topal, Ugur; Dal, Fatih; Kubra Bozkurt, Gamze (Annals of Medical Research, 2021)
Aim: In this study, we aimed to determine the clinical value and prognostic significance of neutrophil / lymphocyte ratio in predicting pancreatic fistula in patients who underwent pancreatoduodenectomy due to periampullary tumor.Material and Methods: Patients who underwent pancreatoduodenectomy for periampullary tumor between 2010-2019 were included in the study. Group 1 (LowNLR) and Group 2 (HighNLR) were formed. Demographic and clinical characteristics, intraoperative and postoperative outcomes, and mean survival were compared between the groups. The significance of NLR in predicting pancreatic fistula at the cut off value was examined.Results: Patients were divided into two groups according to the 3.15 cut off value. Group 1 consisted of 61 patients and Group 2 consisted of 62 patients. In Group 2, albumin gr/dl value was lower (3.25 vs 3.70, p:000). in Group 2 pancreas tumors were more common (59.7% vs 42.6%, p: 0.041). The number of metastatic lymph nodes was higher in Group 1 (1.21 vs 0.63, p: 0.043), and the postoperative pancreatic fistula rate was similar (14.8% vs 21%, p: 0.254). Postoperative complications were higher in Group 2 (41.9% vs 14.8%, p: 0.032) NLR predicted pancreatic fistula with a sensitivity of 31.8% and specificity of 86.4%. In multivariate analysis, we found NLR to be a risk factor for survival (HR 1.760, 95% CI,1.179-2.627; p:0.006).Conclusion: Patients with a preoperative high NLR have a worse prognosis than patients with low NLR. It cannot be used alone to predict pancreatic fistula. NLR has the potential to be used in the management of patients.